The Role Of Environmental Knowledge In Mediating The Influence Of Green Product And Social Media Exposure On Purchase Intention In Denpasar City - I Gusti Agung Shadevaningrat; Nyoman Sri Manik Parasari (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to determine how Environmental Knowledge is able to mediate the influence of Green Product and Social Media Exposure on Purchase Intention on environmentally friendly products in Denpasar City. The sampling technique used is purposive sampling with a total of 160 respondents. This research method uses a quantitative method with data analysis techniques using PLS. From the results of the study it can be concluded that Green Product has a positive and significant effect on Environmental Knowledge, Social Media Exposure has a positive and significant effect on Environmental Knowledge, Green Product has a positive and significant effect on Purchase Intention, Social Media Exposure has a positive and insignificant effect on Purchase Intention, Environmental Knowledge has a positive and significant effect on Purchase Intention, Environmental Knowledge significantly mediates the relationship between Green Product and Purchase Intention, and Environmental Knowledge mediation is not significant on the relationship between Social Media Exposure and Purchase Intention.